1997
DOI: 10.1097/00007632-199706010-00009
|View full text |Cite
|
Sign up to set email alerts
|

The Long-Term Follow-Up of Patients With Klippel-Feil Syndrome and Congenital Scoliosis

Abstract: Only a small number of patients with Klippel-Feil syndrome and congenital scoliosis developed cervical symptoms. No fusion pattern that placed the patient at greater risk for developing symptoms could be identified. Factors that did lead to a greater incidence of cervical symptoms were fusion to the cervicothoracic junction and congenital cervical stenosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
37
1
3

Year Published

2001
2001
2016
2016

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(42 citation statements)
references
References 18 publications
1
37
1
3
Order By: Relevance
“…5 Neurological sequelae can arise later in life, with an estimated incidence of between 22% and 43%. 7,18,19 Pizzutillo et al 20 reported that basilar impression and hypermobility at the upper motion segment were often responsible for myelopathy, but other possible causes of neurological deficits include craniovertebral abnormalities, spinal stenosis and scoliosis. 7,9 Spontaneous fusion of C2 and C3 with occipitalisation of C1 is strongly associated with instability and myelopathy.…”
Section: Discussionmentioning
confidence: 99%
“…5 Neurological sequelae can arise later in life, with an estimated incidence of between 22% and 43%. 7,18,19 Pizzutillo et al 20 reported that basilar impression and hypermobility at the upper motion segment were often responsible for myelopathy, but other possible causes of neurological deficits include craniovertebral abnormalities, spinal stenosis and scoliosis. 7,9 Spontaneous fusion of C2 and C3 with occipitalisation of C1 is strongly associated with instability and myelopathy.…”
Section: Discussionmentioning
confidence: 99%
“…Children with Type I or Type III KlippelFeil syndrome usually suffer from severe accessory defects (Barnes, 1994); not all of them become manifest in bones. In the literature, abnormalities such as neck pain, hypomobility of the neck, fusion of the occipito-atlantal joint, basilar impression, eight cervical vertebrae (Gunderson et al, 1967), skoliosis (often caused by hemivertebrae; Resnick, 2002), renal anomalies, Sprengel's deformity, hearing impairment, synkinesis or heart defects (Hensinger et al, 1974), vasculopathies, diseases of the central nervous system and the skeletal system (Theiss et al, 1997) have all been reported. Furthermore, spina bifida, menigocele, deafness or deafmuteness is frequently mentioned (Everberg et al, 1962), as well as os odontoideum (this is a separation of the odontoid process from the body of the axis; Sherk & Dawoud, 1981).…”
Section: Discussionmentioning
confidence: 99%
“…68 Currently, Klippel-Feil syndrome is observed as a syndrome that unites a heterogeneous group of patients only by the presence of a congenital synostosis of two or more cervical vertebrae. 62,67,69 Attempts have been made to further subdivide this heterogeneous group of patients. For example, Samartzis and colleagues proposed a classification method based on radiological findings found in patients with Klippel-Feil syndrome.…”
Section: Transition To a Modern View Of Klippel-feil Syndromementioning
confidence: 99%